2010
DOI: 10.4012/dmj.2009-089
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of micro push-out bond strengths of two fiber posts luted using simplified adhesive approaches

Abstract: By means of a micro push-out test, this study compared the bond strengths of two types of fiber-reinforced posts cemented with luting cements based on two currently available adhesive approaches as well as evaluated their failure modes. Sixty extracted single-rooted human maxillary central incisor and canine teeth were sectioned below the cementoenamel junction, and the roots were endodontically treated. Following standardized post space preparation, the roots were divided into two fiber post groups and then f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
40
0
13

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 30 publications
(49 reference statements)
5
40
0
13
Order By: Relevance
“…On the contrary, Mumcu et al 73 found that there is significant effect of root region on push-out bond strength. Irrespective of post type, highest bond strength values were achieved in the cervical region, whereas the lowest values were obtained in the apical region.…”
Section: Discussionmentioning
confidence: 95%
“…On the contrary, Mumcu et al 73 found that there is significant effect of root region on push-out bond strength. Irrespective of post type, highest bond strength values were achieved in the cervical region, whereas the lowest values were obtained in the apical region.…”
Section: Discussionmentioning
confidence: 95%
“…In the previous studies that investigated the bond strength of composite resin luting cement to root canal-wall dentin, human teeth were used to simulate the clinical conditions 15,16) . However, human teeth have different lengths and mesiodistal and buccolingual widths 17) .…”
Section: Tooth Specimens and Endodontic Treatmentmentioning
confidence: 99%
“…7 These factors may impair immediate bond strength and durability over time. 2 The use of ethanol as an auxiliary method of conditioning intraradicular dentin has been proposed for controlling dentinal moisture and enhancing bond durability. 8 This technique consists of applying ethanol before applying a two-step self-etching or a three-step etch-and-rinse adhesive system, so that the remaining water may be replaced with ethanol.…”
Section: 5005/jp-journals-10024-1720mentioning
confidence: 99%
“…As a consequence, fractures occur less frequently and in a more favorable manner, meaning that fractures are reparable in most of the cases. 2 However, many factors may affect the bond strength between the fiber post, the cement and the root canal, such as dentin hydration, type of conditioning agent and the cement used as well as length, conformation and diameter of intraradicular retainers, and the different anatomical features, density and orientation of dentinal tubules in different depths of root canal. 2,3,5,6 Additional factors may also represent a significant challenge in the cementation procedures, such as the difficulty of light transmission to the apical portion of the root, the limited direct observation inside the root canal, the difficulty in controlling moisture and the application of adhesive…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation